2008
DOI: 10.1021/jp8000114
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Calculation of Ro-vibrational States:  Methodology and DOCl Application Results

Abstract: An improved Lanczos eigenvalue analysis method has been developed to compute the bound ro-vibrational states for the DOCl system at a total angular momentum of J = 0 and J = 30. In this method, the error norm is used to identify all the true eigenvalues, using the Lanczos algorithm without re-orthogonalization. For ro-vibrational spectroscopy calculations, the comparisons among experimental results, the exact quantum mechanical calculations, and the widely used approximate adiabatic rotation method have been m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…[1][2][3][4][5][6][7] Fluorenone is very sensitive to both the intramolecular and intermolecular interactions, such as hydrogen bonding, polarity, steric interaction, and so forth. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] The photophysical properties of fluorenone with various substitutes at different sites of molecule can be changed markedly. Moreover, their photophysical properties in aprotic and protic solvents are also drastically different from each other.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] Fluorenone is very sensitive to both the intramolecular and intermolecular interactions, such as hydrogen bonding, polarity, steric interaction, and so forth. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] The photophysical properties of fluorenone with various substitutes at different sites of molecule can be changed markedly. Moreover, their photophysical properties in aprotic and protic solvents are also drastically different from each other.…”
Section: Introductionmentioning
confidence: 99%
“…The photophysics and photochemistry of fluorenone and its derivatives were widely investigated in past decades. Fluorenone is very sensitive to both the intramolecular and intermolecular interactions, such as hydrogen bonding, polarity, steric interaction, and so forth. The photophysical properties of fluorenone with various substitutes at different sites of molecule can be changed markedly. Moreover, their photophysical properties in aprotic and protic solvents are also drastically different from each other. It has been demonstrated that fluorenone derivatives are excellent model compounds for the investigation of the intramolecular and intermolecular hydrogen bonding induced deactivation of photoexcited molecules, and details of the quenching processes for the excited state have been revealed. …”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the photophysics and photochemistry of fluorenone (FN) and its derivatives have been widely investigated in the past decade. Fluorenone is very sensitive to both the intramolecular and intermolecular interactions, such as hydrogen bonding, polarity, steric interaction, etc. Biczok et al have extensively reported on the photophysical properties of fluorenone with various substitutes at different sites of fluorenone molecule, and the intramoleuclar and intermolecular hydrogen bonding induced deactivation of photoexcited molecules as well as details of the quenching processes for the excited state. It should be noted that Zhao and co-workers have done benchmark studies in the important field of excited-state hydrogen bonding. In particular, Zhao et al have demonstrated for the first time that the excited-state hydrogen bonding of coumarin chromophore in protic solvents can be significantly strengthened upon photoexcitation, which has been a milestone for the investigation of the hydrogen bonding structures and dynamics in excited states . They also investigated the intramolecular and intermolecular hydrogen bonding in both the singlet and triplet electronic excited states of fluorenone and its derivates as well as some other important organic and biological chromophores in alcoholic solutions and their important roles on the excited-state photophysical processes of these chromophores, such as internal conversion (IC), intersystem crossing (ISC), twisted intramolecular charge transfer (TICT), etc. …”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] At the same time, the photophysics and photochemistry of fluorenone (FN) and its derivatives have been widely investigated in the past decade. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Fluorenone is very sensitive to both the intramolecular and intermolecular interactions, such as hydrogen bonding, polarity, steric interaction, etc. [36][37][38][39][40][41][42] Biczok et al have extensively reported on the photophysical properties of fluorenone with various substitutes at different sites of fluorenone molecule, and the intramoleuclar and intermolecular hydrogen bonding induced deactivation of photoexcited molecules as well as details of the quenching processes for the excited state.…”
Section: Introductionmentioning
confidence: 99%
“…These surfaces are denoted as the N1 potential energy surfaces. To improve the accuracy of the N1 PESs for the calculations of the HOCl spectrum , additional ab initio points for each electronic state have been added mainly in the vicinity of the HOCl equilibrium to refine the N1 PESs. The new refined PESs are denoted N2.…”
Section: Introductionmentioning
confidence: 99%